Stability Analysis of A stage Structure Prey-Predator Model with Hollimg Type IV Functional Response - Naji, Raid; Shalan, Rehab (Iraqi Journal of Science, 2024)
In this paper a stage structure prey-predator model with Hollimg type IV functional response is proposed and analyzed. The local stability analysis of the system is carried out. The occurrence of a simple Hopf bifurcation and local bifurcation are investigated. The global dynamics of the system is investigated with the help of the Lyapunov function. Finally, the analytical obtained results are supported with numerical simulation and the effects of parameters system are discussed. It is observed that, the system has either stable point or periodic dynamics.